Homogenization in fractional elasticity – One spatial dimension. Issue 1 (29th November 2013) - Waurick, Marcus
Abstract: In this note we treat the equations of fractional elasticity in one spatial dimension. After establishing well‐posedness, we use an abstract result in the theory of homogenization to derive effective equations in fractional elasticity with highly oscillating coefficients. The approach also permits the consideration of non‐local operators (in time and space). (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)